Mechanistic basis of the inhibition of SLC11/NRAMP-mediated metal ion transport by bis-isothiourea substituted compounds - Manatschal, Cristina (eLife, 2019)
In humans, the divalent metal ion transporter-1 (DMT1) mediates the transport of ferrous iron across the apical membrane of enterocytes. Hence, its inhibition could be beneficial for the treatment of iron overload disorders. Here we characterize the interaction of aromatic bis-isothiourea-substituted compounds with human DMT1 and its prokaryotic homologue EcoDMT. Both transporters are inhibited by a common competitive mechanism with potencies in the low micromolar range. The crystal structure of EcoDMT in complex with a brominated derivative defines the binding of the inhibitor to an extracellular pocket of the transporter in direct contact with residues of the metal ion coordination site, thereby interfering with substrate loading and locking the transporter in its outward-facing state. Mutagenesis and structure-activity relationships further support the observed interaction mode and reveal species-dependent differences between pro- and eukaryotic transporters. Together, our data provide the first detailed mechanistic insight into the pharmacology of SLC11/NRAMP transporters.